Produksi Enzim Inulinase Khamir Pichia manshurica DUCC Y-015 Dari Tepung Umbi Dahlia (Dahlia variabilis Willd.) Dengan Variasi Konsentrasi Magnesium Sulfat (MgSO4.7H2O) Dan Waktu Inkubasi - Riza Laksita Devi Mutiaratri; W Wijanarka; Sri pujiyanto (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2015)
Dahlia tubers (Dahlia variabilis Willd.) contain inulin which can be hydrolyzed by the inulinase enzyme (E.C.3.2.1.7) into fructose monomer units. Application of inulinase enzyme is used in the production of HFS (High Fructose Syrup) dan FOS (Fructo-oligosaccharides). Inulinase can be produced by several microorganisms including inulinolytic yeast Pichia manshurica DUCC Y-015. One of the factors that influence the production of enzyme inulinase is macro minerals and incubation time on production medium. This study aims to determine the concentration of magnesium sulphate (MgSO4.7H2O) and the most optimal incubation time in producing the inulinase enzyme. The research was carried out experimentally using a Randomized Block Design factorial. The first factor is the concentration MgSO4.7H2O those are 0,5 g/L; 1 g/L; and 1,5 g/L. The second factor is the variation of the incubation time, those are 12 hours; 18 hours; and24 hours, repetition was performed three times. Data were analyzed using ANOVA with 5% significant level(α = 0,05) and Duncan Test for further analysis. The results showed that the variation of the concentration ofMgSO4.7H2O has not been able to increase the production of inulinase enzyme, while the incubation time of18 hours produced the inulinase enzyme activity of 0,9605 IU/mL. Keywords: Inulinase, Dahlia variabilis Willd., Pichia manshurica DUCC Y-015, MgSO4, Incubation Time